Recent advances in ultrasound-triggered therapy. (2nd January 2019) - Yang, Chaopin; Li, Yue; Du, Meng; Chen, Zhiyi
Abstract: As a non-invasive and real-time diagnostic technique, ultrasound has provided a novel strategy for targeted treatment. With the rapid development of ultrasonic technique and ultrasound contrast agents (UCAs), spatiotemporally controllable application of ultrasound with or without UCAs makes it possible for site-specific delivery of therapeutic agents and targeted modulation with minimal side effects, which indicated a promising therapy in clinical use. This review will describe the main mechanism of targeted therapy induced by ultrasound briefly, then focus on the current application of ultrasound mediated targeted therapy in various fields including tumour, cardiovascular disease, central nervous system, skeletal muscle system diseases and stem cells therapy. In addition, ongoing challenges of ultrasound-mediated targeted therapy for further research and its clinical use are reviewed.